2018
DOI: 10.1002/hep4.1181
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of insulin‐like growth factor 1 receptor enhances the efficacy of sorafenib in inhibiting hepatocellular carcinoma cell growth and survival

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common primary cancer and second largest cause of cancer‐related death worldwide. The first‐line oral chemotherapeutic agent sorafenib only increases survival in patients with advanced HCC by less than 3 months. Most patients with advanced HCC have shown limited response rates and survival benefits with sorafenib. Although sorafenib is an inhibitor of multiple kinases, including serine/threonine‐protein kinase c‐Raf, serine/threonine‐protein kinase B‐Raf, vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…One of the main causes of sorafenib resistance in HCC is increased growth factor signaling, including IGF/IGF-1R signaling. Although sorafenib inhibits several tyrosine kinases, it does not suppress IGF-1R phosphorylation in HCC cells [ 232 , 233 ]. Sorafenib treatment of Hep3B, HepG2, or Huh7 cells showed no change in levels of IGF-1R phosphorylation.…”
Section: Igf/igf-1r Signaling Responses For Targeted-drugs Resistamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main causes of sorafenib resistance in HCC is increased growth factor signaling, including IGF/IGF-1R signaling. Although sorafenib inhibits several tyrosine kinases, it does not suppress IGF-1R phosphorylation in HCC cells [ 232 , 233 ]. Sorafenib treatment of Hep3B, HepG2, or Huh7 cells showed no change in levels of IGF-1R phosphorylation.…”
Section: Igf/igf-1r Signaling Responses For Targeted-drugs Resistamentioning
confidence: 99%
“…Sorafenib treatment of Hep3B, HepG2, or Huh7 cells showed no change in levels of IGF-1R phosphorylation. Meanwhile, knocking down IGF-1R by shRNA or preventing IGF-1R phosphorylation by ceritinib enhanced the efficacy of sorafenib, reducing cell proliferation rate and tumor development [ 232 ]. Suppression of IGF/IGF-1R signaling induced sorafenib sensitivity in HCC cells.…”
Section: Igf/igf-1r Signaling Responses For Targeted-drugs Resistamentioning
confidence: 99%
“…Since blood insulin-like growth factor 1 (IGF-1) is mainly produced by the liver, our previous studies [27][28][29], in line with reports from other groups [30][31][32][33][34], have demonstrated that IGF-1 is a surrogate biomarker for the synthetic function of the liver, the status of underlying chronic liver diseases, and a significant predictor of OS in patients with chronic liver disease and HCC. Moreover, the expression of IGF-1R is upregulated in HCC, and in vitro studies have demonstrated reduction in tumor growth by inhibition of IGF-1 [35][36][37][38]. In accordance with these findings, lower baseline IGF-1 correlates with worse OS in HCC patients, irrespective of liver dysfunction, and data suggest that IGF-1 levels are useful in identifying HCC patients at greater risk of relapse following TACE or liver resection [39,40].…”
Section: Introductionmentioning
confidence: 54%
“…All cells were cultured as described previously. 6 For knockdown experiments, Huh7 and Hep3B cells were infected with lentiviral pLKO.1 particles, which contain ABL1, NOTCH1, c-MYC, or scrambled short hairpin RNA (shRNA) and selected with 2 mg/mL puromycin for 5 days. Lentiviral pLKO.1 plasmids for shABL1 (Supplementary Table 1), shNOTCH1 (Supplementary Table 1), shc-MYC, 7 or scrambled shRNA (SHC002; Sigma-Aldrich, St Louis, MO) were packaged with pCMV-dr8.2 (Addgene, Watertown, MA) and pCMV-VSVG (Addgene) in 293T cells to produce lentiviral particles, as described previously.…”
Section: Cells and Treatmentsmentioning
confidence: 99%
“…The proliferation of these cells was then analyzed using ala-marBlue assay, as described previously. 6 For experiments involving the overexpression of c-MYC, the pBpuro c-MycER retroviral plasmid (gifted from Dr Gerard Evan) 8 and control pBpuro retroviral plasmids (Addgene, #1764) were packaged with pMD.MLV and pMD.G/pVSV.G in 293T cells to produce retroviral particles. Six days after infection with the retroviral particles, scrambled and ABL1-KD Huh7 cells were treated with 100 nM 4-hydroxytamoxifen.…”
Section: Cells and Treatmentsmentioning
confidence: 99%